Descrição da construção insubordinada com “se ao menos” no português brasileiro a partir da análise colostrucional - Comarim, Maria Julia Bernardo (Universidade Federal de São Carlos, 2023)
In this course conclusion work, the conditional constructions headed by [se ao menos] (if only) are analyzed quali quantitatively. Unlike those in which the main clause is expressed, they only admit verbs in the imperfect subjunctive, something that Hirata-Vale (2015) pointed out as a structural indicator of constructions that tend towards insubordination (EVANS, 2007). To investigate this trend, it was proposed to carry out a collostructional analysis, defined by Hilpert (2014) as a possibility within the methods presented by Corpus Linguistics, which aims to discover which lexical items co-occur with a given construction. The expectation is that this information will allow a better understanding of the insubordinate constructions headed by [se ao menos], to describe in greater detail such use, in addition to proposing a categorization of this type of constructions. For the research proposed here, a corpus to be analyzed was constituted from real occurrences from the Corpus do Português (CdP) (DAVIES & FERREIRA, 2016), from the session Web/Dialects, adding occurrences found in tweets. The corpus is synchronic and the occurrences from CdP were collected between 2013 and 2014, and tweets were collected between 2021 and 2022.This investigation is justified by the need to expand the linguistic knowledge related to regular constructions in Brazilian Portuguese (BP), scarcely described by theory, using an analysis method not very explored in Brazil (ALONSO, OLIVEIRA, FUMEAUX, 2019). With the results, it was possible to work with a semantic cluster of some of the most attracted verbs (saber, poder e conseguir), which were understood as belonging to the capacity frame, in the FrameNetBR classification (SALOMÃO, 2020). In addition, the existence of ironic desires was attested, a use not yet described in theory for other languages. Finally, this work dialogues with projects already developed and under development on the subject in BP, such as Hirata-Vale (2017), Coimbra (2019), Coradini (2019, 2021, 2022), Alves (2019) and Comarim e Hirata-Vale (2023).
Description of the insubordinate construction with “se ao menos” in Brazilian Portuguese based on colostruccional analysis
Keywords: Insubordinação; Análise colostrucional; Sintaxe funcional; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA